Developing Variation in Gilles Tremblay’s Croissant: Transformation and Identity - Lind, Stephanie (Intersections)

(untitled) (Canadian University Music Society / Société de musique des universités canadiennes, 2017)
Gilles Tremblay, considered one of the forefathers of contemporary music in Quebec, is primarily known for a focus on rhythm, sonority, and aleatoric processes. This article explores another unexplored aspect of Tremblay’s composition: motivic development through developing variation. Beginning with a discussion of the historical antecedents of this style in the work of Schoenberg, d’Indy, and Dutilleux, the article analyzes Tremblay’s use of developing variation in his string quartet, Croissant, through the lens of transformational theory.